Retrospective Study of Patients With SJS/TEN Treated at a Tertiary Burn Unit in Canada: Overview of 17 Years of Treatment. Issue 3 (May 2021) - Olteanu, Cristina; Shear, Neil H.; Burnett, Marjorie; Hashimoto, Rena; Jeschke, Marc G.; Ziv, Michael; Dodiuk-Gad, Roni P.
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are adverse drug reactions. Objectives: To learn about the clinical characteristics of patients with SJS/TEN including treatments provided, outcomes, and mortality. Methods: We conducted a retrospective chart review of patients who were hospitalized with the diagnosis of SJS/TEN at the Ross Tilley Burn Center between the years 1999 and 2015. Results: A total of 43 patients were identified with a mean age of 54 ± 19 (58, 18-85). The most common offending medications were allopurinol and carbamazepine. The overall mortality rate in our study is 21% with the most common causes of death being multiorgan failure and sepsis. The majority of our patients had oral (84%), ocular (79%), and genital (60%) involvement during hospitalization. Our data revealed that combination treatment involving oral corticosteroids with intravenous immunoglobulin (IVIG) had the highest mortality rate in our study since 55% (6/11) of patients who were treated in this manner passed away compared to 11% (2/18) of patients passing away who were treated with solely IVIG and 33% (1/3) who were treated with only supportive care. Our study also demonstrates the addition of etanercept and cyclosporine treatment in the second time period we studied: 2008-2015 versus the earlier time period of 1999-2007. None of the patients in our study who were treated with therapies including cyclosporine and/or etanercept passed away. Conclusions: Our study sheds light on a possible beneficial role of cyclosporine and etanercept for the treatment of SJS and TEN and reinforces the necessity of a multidisciplinary care team for patients.